Pengaruh Elemen-Elemen Good Corporate Governance Dan Independensi Auditor Terhadap Integritas Laporan Keuangan - Annisa Qatrunnada; Gustati; Randy Heriyanto (Journal of Applied Accounting And Business, 2024)
This research aims to determine the influence of elements of good corporate governance and auditor independence on the integrity of financial reports. The measurement of financial report integrity in this study uses the conservatism index. This research is a quantitative descriptive research and multiple linear regression analysis method using SPSS version 24. The population of this research are companies in the non-cyclical consumer sector which are listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique in this research used the purposive sampling method. The research results show that the elements of good corporate governance, namely the managerial ownership variable, and the auditor independence variable have a positive effect on the integrity of financial reports. Meanwhile, the elements of good corporate governance, namely institutional ownership, independent commissioners and audit committee variables, have no effect on the integrity of financial reports. However, simultaneously, the elements of good corporate governance institutional ownership, managerial ownership, independent commissioners, audit committees and auditor independence simultaneously influence the integrity of financial reports.